Synthesis of New 3-Arylaminophthalides and 3-Indolyl-phthalides using Ammonium Chloride, Evaluation of their Anti-Mycobacterial Potential and Docking Study - Patil, Avinash; Duggal, Harleen; Bagul, Kamini T.; Kamble, Sonali; Lokhande, Pradeep; Gacche, Rajesh; Meshram, Rohan (Combinatorial Chemistry & High Throughput Screening, 2020)
Objective: The study aims at the derivatization of “Phthalides” and synthesizes 3- arylaminophthalides & 3-indolyl-phthalides compounds, and evaluates their anti-tubercular and antioxidant activities. The study has also intended to employ the in silico methods for the identification of possible drug targets in Mycobacterium and evaluate the binding affinities of synthesized compounds. Methods: This report briefly explains the synthesis of phthalide derivatives using ammonium chloride. The synthesized compounds were characterized using spectral analysis. Resazurin Microtiter Assay (REMA) plate method was used to demonstrate the anti-mycobacterial activity of the synthesized compounds. An in-silico pharmacophore probing approach was used for target identification in Mycobacterium. The structural level interaction between the identified putative drug target and synthesized phthalides was studied using Lamarckian genetic algorithm-based software. Results and Discussion: In the present study, we report an effective, environmentally benign scheme for the synthesis of phthalide derivatives. Compounds 5c and 5d from the current series appear to possess good anti-mycobacterial activity. dCTP: deaminasedUTPase was identified as a putative drug target in Mycobacterium. The docking results clearly showed the interactive involvement of conserved residues of dCTP with the synthesized phthalide compounds. Conclusion: On the eve of evolving anti-TB drug resistance, the data on anti-tubercular and allied activities of the compounds in the present study demonstrates the enormous significance of these newly synthesized derivatives as possible candidate leads in the development of novel anti-tubercular agents. The docking results from the current report provide a structural rationale for the promising anti-tubercular activity demonstrated by 3-arylaminophthalides and 3-indolyl-phthalides compounds.
Keywords: 3-arylaminophthalides